Revealing Dengue Risk Factors in Cilacap Regency, Central Java - Farida Hasna; Siwi Pramatama Mars; Eko Hendarto; Suzina Yatapya (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2021)
Dengue virus (DENV) infection is still an important health problem in Indonesia, it is important to identify the specific risk factors in an area. The aims of this study is to analyze the risk factors for DENV infection from various variables such as mobility, preventive behavior, house conditions, occupancy density and the presence of mosquito larvae. This is a case control design, involves 64 cases and 64 control in Cilacap Regency, Central Java. Variables this study were mobility, practice of dengue prevention, ventilation area, occupancy density and presence of mosquito larvae. Data collection was carried out by questionnaire, observation and epidemiology investigation form. Results of this study showed that the existence of Aedes sp larvae and dengue prevention practice as significant factors contributed to the DENV infection in the research area. This research highlighted the importance of dengue prevention and control and human practice as a common denominator to minimize the risk of contracting dengue.